Mobile mural thrombus and spontaneous echo contrast in ascending aorta after postoperative adjuvant cisplatin‐based chemotherapy. Issue 6 (21st May 2020) - Aoyama, Yutaka; Harada, Kenji; Yokoyama, Yasuhiro; Ishiyama, Yusuke; Komori, Takahiro; Shimpo, Masahisa; Kario, Kazuomi
Abstract: A 70‐year‐old asymptomatic male who had undergone a right nephrectomy for renal pelvic cancer was referred to us with a thrombus in the ascending aorta detected by contrast‐enhanced computed tomography after chemotherapy with gemcitabine/cisplatin. Transesophageal echocardiography revealed a 4‐cm mobile mural thrombus in the ascending aorta. An emergency thoracotomy for planned aortic root replacement was performed, but the intraoperative epi‐aortic ultrasound indicated that the thrombus had disappeared, and it showed prominent spontaneous‐echo contrast (SEC) in the ascending aorta. We speculate that vascular endothelium damage due to the cisplatin‐based chemotherapy induced the thrombus and SEC in the ascending aorta.